REALISASI KESANTUNAN BERBAHASA DALAM FILM SURGA YANG TAK DIRINDUKAN 2 - Dewantari, Resti; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study describes the realization of politeness in language in the film Surga yang Tak Dirindukan 2. Politeness is a procedure for communicating through language procedures. Politeness is also used as a benchmark for speakers of speech partners. The purpose of this research is to describe illocutionary speech acts, forms of language politeness speech, and the strategies of speakers in realizing language politeness.The theory used in this study is Leech's theory using the maxim theory in the politeness principle. This type of research is qualitative. The form of this research is descriptive. The research approach used is the pragmatic approach.Based on the analysis results in the film Surga yang tak dirindukan 2 concluded that there are 23 kinds of speech acts that are divided into four kinds of speech acts namely, assertive, directive, commissive and expressive. Forms of politeness politeness speech are in 5 forms of speech acts: politeness politeness speech in reminding, politeness politeness speech in suggesting, politeness politeness speech in offering, politeness politeness speech in pledging, and politeness politeness speech in praise. The politeness strategies of language there are five strategies which are divided into two, positive politeness strategies and negative politeness strategies: the strategy of realizing positive politeness: a) offering help or promises, b) using group identity markers, and c) giving praise and realization of negative politeness strategies: a ) apologies, and b) being pessimistic. Keywords: Realization of Politeness, Speech Act, Politeness Strategy, Film Surga yang Tak Dirindukan 2.